Answer:
-no solution-
Explanation:
Let's solve your system by elimination.
−6x+2y=−14;−9x+3y=−21
Multiply the first equation by 3,and multiply the second equation by -2.
3(−6x+2y=−14)
−2(−9x+3y=−21)
Becomes:
−18x+6y=−42
18x−6y=42
Add these equations to eliminate y:
0=0
Answer:
Infinitely many solutions.
Let's solve your system by substitution.
−6x+2y=−14;−9x+3y=−21
Step: Solve−6x+2y=−14for x:
−6x+2y=−14
−6x+2y+−2y=−14+−2y(Add -2y to both sides)
−6x=−2y−14
−6x
−6
=
−2y−14
−6
(Divide both sides by -6)
x=
1
3
y+
7
3
Step: Substitute
1
3
y+
7
3
forxin−9x+3y=−21:
−9x+3y=−21
−9(
1
3
y+
7
3
)+3y=−21
−21=−21(Simplify both sides of the equation)
−21+21=−21+21(Add 21 to both sides)
0=0
Answer:
Infinitely many solutions.